2019
DOI: 10.1029/2018ms001567
|View full text |Cite
|
Sign up to set email alerts
|

A Transient Coupled Ice Flow‐Damage Model to Simulate Iceberg Calving From Tidewater Outlet Glaciers

Abstract: Iceberg calving, the detachment of an ice block at the glacier front, is the main process responsible for the dynamic mass loss from the ice sheets to the ocean. Understanding this process is essential to accurately predict ice sheet response to the future climate. We present a transient multiphysics finite-element model to simulate iceberg break-off and geometry evolution of a marine-terminating glacier. The model solves the coupled equations of ice flow, damage mechanics, oceanic melt, and geometry evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 69 publications
4
18
0
Order By: Relevance
“…Ma and Bassis () found both an enhancing and a suppressing effect of melt on calving, depending on magnitude and vertical distribution of melt, but their simulation was limited to the onset phase of one calving event. Our own preliminary experiments with a transient Lagrangian ice flow and damage‐based calving model showed similar effects and indicated that the relationship between submarine melt and iceberg calving may not be as straightforward as previously thought (Mercenier et al, ). However, that study lacked a systematic investigation of the influence of oceanic melt rates on calving flux and frontal volume loss.…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…Ma and Bassis () found both an enhancing and a suppressing effect of melt on calving, depending on magnitude and vertical distribution of melt, but their simulation was limited to the onset phase of one calving event. Our own preliminary experiments with a transient Lagrangian ice flow and damage‐based calving model showed similar effects and indicated that the relationship between submarine melt and iceberg calving may not be as straightforward as previously thought (Mercenier et al, ). However, that study lacked a systematic investigation of the influence of oceanic melt rates on calving flux and frontal volume loss.…”
Section: Introductionsupporting
confidence: 70%
“…We employ the transient Lagrangian multiphysics calving model developed in Mercenier et al () in two and three dimensions. This model is implemented using the libMesh finite element library (Kirk et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A. Köhler et al: Seismic calving quantification 2012;Köhler et al, 2015), hydroacoustic (Glowacki et al, 2015), and water surface wave monitoring (Minowa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%